1969
DOI: 10.1039/qr9692300504
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for nucleophilic and photonucleophilic aromatic substitution reactions

Abstract: The term 'ground state' in this Review is used to indicate electronic ground state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
27
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(28 citation statements)
references
References 5 publications
1
27
0
Order By: Relevance
“…1 It was found that two or three nitro groups exert a very powerful effect so that 2,4,6-trinitrochlorobenzene and acyl chloride are comparable in hydrolytic reactivity whereas chlorobenzene requires a higher temperature for hydrolysis. 4,[11][12][13][14][15][16][17] This increase in liability of pyridines to nucleophilic attack is a further reflection for the electronattracting character of the ring nitrogen. [8][9][10] Pyridine derivatives undergo nucleophilic substitution much more easily than the corresponding benzenes, owing to the presence of an electronegative nitrogen atom in the aromatic ring, specially at both 2-and 4positions.…”
Section: Introductionmentioning
confidence: 99%
“…1 It was found that two or three nitro groups exert a very powerful effect so that 2,4,6-trinitrochlorobenzene and acyl chloride are comparable in hydrolytic reactivity whereas chlorobenzene requires a higher temperature for hydrolysis. 4,[11][12][13][14][15][16][17] This increase in liability of pyridines to nucleophilic attack is a further reflection for the electronattracting character of the ring nitrogen. [8][9][10] Pyridine derivatives undergo nucleophilic substitution much more easily than the corresponding benzenes, owing to the presence of an electronegative nitrogen atom in the aromatic ring, specially at both 2-and 4positions.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of o-complexes which are For personal use only. closely analogous to 3 and 4 have been characterized by nmr as well as uv-vis spectroscopy (1)(2)(3)(4)(5)(6)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). However, there is as yet no unambiguous uv-vis or nmr evidence for the carbanions 5 and 6.…”
mentioning
confidence: 99%
“…The capability of aromatic nitro compounds to interact with bases by a number of mechanisms has led to controversy regarding the occurrence and importance of nuclear hydrogen exchange (1)(2)(3)(4)(5)(6). In the case of 1,3-dinitrobenzene (DNB), the species that have been postulated to be formed at different times through action of a base Y: are a charge transfer complex 1, a radical anion 2, covalent adducts (also known as Meisenheimer or o-complexes) 3 and 4, as well as the carbanions 5 and 6 which are the presumed intermediates in proton exchange.…”
mentioning
confidence: 99%
“…NO,, CN etc., as a general condition for the adduct 2 to be a spectrally detectable species. In cases where X is a displaceable group, these adducts are believed to be formed as reaction intermediates in the overall nucleophilic aromatic substitution (SNAr) process (8)(9)(10).…”
mentioning
confidence: 99%